Cell Chirality Drives Left-Right Asymmetric Morphogenesis - Inaki, Mikiko; Sasamura, Takeshi; Matsuno, Kenji (Frontiers in Cell and Developmental Biology, 2018)
Most macromolecules found in cells are chiral, meaning that they cannot be superimposed onto their mirror image. However, cells themselves can also be chiral, a subject that has received little attention until very recently. In our studies on the mechanisms of left-right (LR) asymmetric development in Drosophila, we discovered that cells can have an intrinsic chirality to their structure, and that this “cell chirality” is generally responsible for the LR asymmetric development of certain organs in this species. The actin cytoskeleton plays important roles in the formation of cell chirality. In addition, Myosin31DF (Myo31DF), which encodes Drosophila Myosin ID, was identified as a molecular switch for cell chirality. In other invertebrate species, including snails and Caenorhabditis elegans, chirality of the blastomeres, another type of cell chirality, determines the LR asymmetry of structures in the body. Thus, chirality at the cellular level may broadly contribute to LR asymmetric development in various invertebrate species. Recently, cell chirality was also reported for various vertebrate cultured cells, and studies suggested that cell chirality is evolutionarily conserved, including the essential role of the actin cytoskeleton. Although the biological roles of cell chirality in vertebrates remain unknown, it may control LR asymmetric development or other morphogenetic events. The investigation of cell chirality has just begun, and this new field should provide valuable new insights in biology and medicine.